Movement patterns of white seabass Atractoscion nobilis tagged along the coast of Baja California, Mexico - Scott A. Aalbers; Oscar Sosa-Nishizaki; Justin E. Stopa; Chugey A. Sepulveda (Environmental Biology of Fishes, 2022)

An Integrated Observing System for Monitoring Marine Debris and Biodiversity - Nikolai Maximenko; Artur Palacz; Lauren Biermann; James Carlton; Luca Centurioni; Mary Crowley; Jan Hafner; Linsey Haram; Rebecca Helm; Verena Hormann; Cathryn Murray; Gregory Ruiz; et al. (Oceanography, 2021)

Coastal Sea Level and Related Fields from Existing Observing Systems - Marta Marcos; Guy Wöppelmann; Andrew Matthews; Rui M. Ponte; Florence Birol; Fabrice Ardhuin; Giovanni Coco; Alvaro Santamaría-Gómez; Valerie Ballu; Laurent Testut; Don Chambers; Justin E. Stopa (Surveys in Geophysics, 2019)

Observing Sea States - Fabrice Ardhuin; Justin E. Stopa; Bertrand Chapron; Fabrice Collard; Romain Husson; Robert E. Jensen; Johnny Johannessen; Alexis Mouche; Marcello Passaro; Graham D. Quartly; Val Swail; Ian Young (Frontiers in Marine Science, 2019)

Measuring currents, ice drift, and waves from space: the Sea surface KInematics Multiscale monitoring (SKIM) concept - Fabrice Ardhuin; Yevgueny Aksenov; Alvise Benetazzo; Laurent Bertino; Peter Brandt; Eric Caubet; Bertrand Chapron; Fabrice Collard; Sophie Cravatte; Jean-Marc Delouis; Frederic Dias; Gérald Dibarboure; et al. (Ocean Science, 2018)
We propose a satellite mission that uses a near-nadir Ka-band Doppler radar to measure surface currents, ice drift and ocean waves at spatial scales of 40 km and more, with snapshots at least every day for latitudes 75 to 82°, and every few days for other latitudes. The use of incidence angles of 6 and 12° allows for measurement of the directional wave spectrum, which yields accurate corrections of the wave-induced bias in the current measurements. The instrument's design, an algorithm for current vector retrieval and the expected mission performance are presented here. The instrument proposed can reveal features of tropical ocean and marginal ice zone (MIZ) dynamics that are inaccessible to other measurement systems, and providing global monitoring of the ocean mesoscale that surpasses the capability of today's nadir altimeters. Measuring ocean wave properties has many applications, including examining wave–current interactions, air–sea fluxes, the transport and convergence of marine plastic debris and assessment of marine and coastal hazards.